Design, Synthesis and Anticancer Activity of New Benzofuran-Chalcone Hybrids and Their Water Soluble Sodium Salts - Cinar-Asa, Sibel; Coskun, Demet; Akgun, Oguzhan; Akgun, Halime; Coskun, Mehmet Fatih; Ari, Ferda (Wiley-V C H Verlag Gmbh, 2023)
In this study, firstly, 1-(7-ethoxy-1-benzofuran-2-yl) ethanone and 1,1'-(7-ethoxy-1-benzofuran-2,4-diyl)diethanone were synthesized for the starting reagent purposes. The synthesized benzofuran-chalcone salts were soluble in water at room temperature. Structural analysis of the synthesized compounds was characterized by elemental analysis, FT-IR and NMR spectroscopy techniques. The anticancer activities of the compounds were determined by SRB viability assay in human lung cancer (A549, H1299) and breast cancer (MCF-7, MDA-MB-231) cell lines. Findings for apoptosis were determined by flow cytometry analysis and the PARP-ELISA method. The results of the in vitro SRB analysis of the compounds showed that some of the chalcone hybrids were very effective on both types of cancer in a dose and time-dependent manner. Treatment of all cancer cell types with these hybrids resulted in a significant increase in the percentage of early and mainly late apoptotic cells, demonstrating their apoptosis-inducing effects via the Caspase 3/7 Activity.
Keywords: Anticancer activity; apoptosis; benzofuran; chalcone; cytotoxicity